OPTIMIZATION OF DETERMINING MAINTENANCE INTERVALS WITH THE MARKOV CHAIN METHOD TO MINIMIZE MAINTENANCE COSTS IN PT. BBI - Dwi Qomariah Arifin; Enny Aryanny (Center for Study and Journal Management FTI UMI, 2022)
PT BBI is a company engaged in producing machinery, industrial equipment, and foundry. PT BBI has overgrown as a company that focuses on manufacturing and delivering products such as oil and gas/refinery/petrochemical industries, power plans, iron castings, precision machinery centers, etc. PT BBI uses various kinds of machines to support its production process. Some devices have often experienced damage and caused downtime in recent years, namely radial drilling machines and overhead cranes. In addition, machine damage also causes cost overruns due to damage that can harm the company. Engine damage caused is due to the company's poor maintenance policy. Judging from these problems, planning a maintenance system with a suitable method will help the machines and production equipment owned by PT. BBI is protected from damage that occurs periodically. The Markov Chain method was chosen because it has advantages over other maintenance methods because it produces more optimal maintenance costs with a regular maintenance scheduling system. The processing results obtained a total savings of 33% by applying the Markov Chain proposed maintenance method with maintenance intervals every 5 months for radial drilling machines and once every 3 months for 10T overhead cranes